Acute coronary syndromes. Issue 10332 (2nd April 2022) - Bergmark, Brian A; Mathenge, Njambi; Merlini, Piera A; Lawrence-Wright, Marilyn B; Giugliano, Robert P
Summary: Although substantial progress has been made in the diagnosis and treatment of acute coronary syndromes, cardiovascular disease remains the leading cause of death globally, with nearly half of these deaths due to ischaemic heart disease. The broadening availability of high-sensitivity troponin assays has allowed for rapid rule-out algorithms in patients with suspected non-ST-segment elevated myocardial infarction (NSTEMI). Dual antiplatelet therapy is recommended for 12 months following an acute coronary syndrome in most patients, and additional secondary prevention measures including intensive lipid-lowering therapy (LDL-C <1·4 mmol/L), neurohormonal agents, and lifestyle modification, are crucial. The scientific evidence for diagnosis and management of acute coronary syndromes continues to evolve rapidly, including adapting to the COVID-19 pandemic, which has impacted all aspects of care. This Seminar provides a clinically relevant overview of the pathobiology, diagnosis, and management of acute coronary syndromes, and describes key scientific advances.